Enhancing ASTM B424 UNS N08825 Long Seam Weld Liner Material with Annealing Quenching Techniques in the Cladding Process on the Surface of Steel Pipes - Yunasri, Yunasri; Hasibuan, Fardin; Hakim, Arif Rahman; Ariyanto, Nugroho Pratomo (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2024)
The use of cladding methods in manufacturing corrosion-resistant pipes is crucial for industries such as oil and gas, chemical plants, and pressure vessel manufacturing. This study focuses on ASTM B424 UNS N08825, a corrosion-resistant alloy (CRA) to be used as the surface layer for steel pipes. The cladding method involves forming CRA sheets into longitudinal pipes, followed by welding the joints, annealing, and rapid cooling before high process expansion to surface layer the steel pipes. At a temperature of 930-990°C, the annealing process aims to reduce stress and improve material properties, followed by rapid cooling to stabilize the microstructure. Various tests were conducted on the CRA liner pipes with or without annealing and quenching, including tensile testing, hardness testing, chemical composition analysis, and microstructure examination. The results showed that the material's ultimate tensile strength and hardness significantly increased after the treatment, with better uniformity in the microstructure. This study concludes that annealing and rapid cooling enhance the mechanical properties and stability of ASTM B424 UNS N08825, allowing the cladding process on steel pipe surfaces to be performed flawlessly and making it suitable for high-performance applications in corrosive environments.